Inóculos bacterianos: una alternativa para mejorar el proceso fermentativo en los ensilajes tropicales - Tobía-Rivero, Carlos (Universidad de Costa Rica, 2013)
Milk Production systems depend on good quality forages. Silage is a great alternative for storing forages throughout the year. The fermentation process in silage, presents four phases (aerobic, fermentative, stabilization and deterioration). The use of lactic acid producing bacteria, as an additive helps optimizing the fermentation process. Specially when tropical forages are used, due to the lower natural concentration of lactic acid bacteria and fermentable carbohydrates. These additives stimulate fermentation and decrease aerobic deterioration. Forages or other products stored as silage suffer damage and a reduction in its nutritional values as well as risk in pollution. Therefore, increasing stabilization in silage is of great interest of producers for forage conservation.